Cervical vertebral hyperostosis and difficult direct laryngoscopy in a patient for primary thyroplasty. Issue 2 (4th August 2013) - Turnbull, James; Hughes, Owain; Rubin, John; Patel, Anil
Summary: Diffuse idiopathic skeletal hyperostosis is a disease typified by calcification of ligamentous structures, predominantly in the spine. In the cervical spine, large congruous osteophyte formation anterior to the vertebral bodies can cause significant changes to airway anatomy. Difficult facemask ventilation, direct laryngoscopy and LMA positioning have all been reported. Primary thyroplasty involves medialisation of an immobile vocal cord in order to improve voice production. An unobstructed view of the vocal cords is important to aid implant insertion but can complicate airway management. We present the case of an elderly patient undergoing primary thyroplasty with cervical vertebral hyperostosis, dysphagia, immobile vocal cord and difficult direct laryngoscopy. This case highlights the intricacies involved when anaesthetising a patient for complex vocal cord surgery with abnormal airway anatomy.